2019
DOI: 10.31235/osf.io/e92ha
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Actual Risk of Bystander Intervention: A Statistical Study Based on Naturally Occurring Violent Emergencies

Abstract: Objectives: Bystander studies have rarely considered the victimization risk associated with intervention into violent, dangerous emergencies. To address this gap, we aim to identify factors that influence bystanders' risk of being physically victimized. Methods:We observed bystander behavior from video surveillance footage of naturally occurring violence in night-time economy settings, and data was analyzed with a logistic regression model. Results: Data shows that approximately one out of six interventions re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 35 publications
2
46
1
1
Order By: Relevance
“…Qualitative interviews, by comparison, tend to be conducted in a more open-ended, typically semistructured manner, that allows finer-grained explorative accounts of experiences (Lindegaard, Bernasco, & Jacques, 2015;Wellington & Szczerbinski, 2007). Qualitative interviews may be obtained from secondary sources, e.g., victim and offender statements in police case files (Liebst, Heinskou, & Ejbye-Ernst, 2018;Weenink, 2014), but are mainly conducted by the academic scholars themselves. Such interviews have been utilized to examine the conflict experiences of all social roles in the NTE, including perpetrators (Graham & Wells, 2003;Hochstetler, Copes, & Forsyth, 2014), victims (Nicholls, 2017), bystanders (Levine et al, 2012), NTE staff (Hobbs, O'Brien, & Westmarland, 2007), and key NTE informants (e.g, the police, liquor licensees, council workers; Miller et al, 2012).…”
Section: Self-reports: Surveys and Interviewsmentioning
confidence: 99%
See 3 more Smart Citations
“…Qualitative interviews, by comparison, tend to be conducted in a more open-ended, typically semistructured manner, that allows finer-grained explorative accounts of experiences (Lindegaard, Bernasco, & Jacques, 2015;Wellington & Szczerbinski, 2007). Qualitative interviews may be obtained from secondary sources, e.g., victim and offender statements in police case files (Liebst, Heinskou, & Ejbye-Ernst, 2018;Weenink, 2014), but are mainly conducted by the academic scholars themselves. Such interviews have been utilized to examine the conflict experiences of all social roles in the NTE, including perpetrators (Graham & Wells, 2003;Hochstetler, Copes, & Forsyth, 2014), victims (Nicholls, 2017), bystanders (Levine et al, 2012), NTE staff (Hobbs, O'Brien, & Westmarland, 2007), and key NTE informants (e.g, the police, liquor licensees, council workers; Miller et al, 2012).…”
Section: Self-reports: Surveys and Interviewsmentioning
confidence: 99%
“…In order to investigate naturally occurring behavior of individuals during NTE mid-violent events, and to partially address the ecological validity concerns of experimental studies and the reliability issues of self-reported studies, some scholars have advocated for naturalistic observations of NTE violence (Graham et al, 2006;Levine et al, 2011;Liebst, Heinskou, et al, 2018;Philpot, 2017).…”
Section: Observations: On-site Non-participatory and Participatory Apmentioning
confidence: 99%
See 2 more Smart Citations
“…Alongside the meta-analytical work highlighting the importance of danger for bystander intervention, studies more recently examine bystander involvement in the dangerous setting of real-life public violence. Here, the methods employed include assessments of police case file descriptions of public violent assaults , interviews with bystanders (Levine, Lowe, Best, & Heim, 2012), on-site observations of bystander involvement (Parks, Osgood, Felson, Wells, & Graham, 2013), and video observations of street violence using surveillance camera footage (Levine, Taylor, & Best, 2011;Liebst, Heinskou, & Ejbye-Ernst, 2018;Philpot, 2017). The latter video-based method, offers a unique possibility to systematically study how violent interactions unfold chronologically and how bystanders shape the ongoing situation .…”
Section: Introductionmentioning
confidence: 99%